Perinatal dengue in a neonate with multiple comorbidities: case report and literature review - Li, Guanghong; Du, Xiaoqun; Luo, Weibin; Wei, Junhua; Huang, Huiyi (Frontiers in Pediatrics, 2025)
BackgroundDengue is an increasingly common arboviral infection in endemic regions and can affect pregnant women. Neonatal presentations are uncommon and often overlap with other perinatal conditions such as meconium-related lung disease and early-onset bacterial infection, complicating diagnosis and management.Case presentationWe report a term male neonate born through meconium-stained amniotic fluid to a mother with late-pregnancy dengue. Within hours, the infant developed tachypnea and coarse rales. Initial studies showed metabolic acidosis and coagulopathy; chest radiography demonstrated bilateral patchy opacities. A working diagnosis of meconium aspiration syndrome was made, and empiric penicillin, oxygen, and supportive care were initiated. On day 2, dengue NS1 antigen tested positive; Respiratory PCR detected low-level Ureaplasma urealyticum, though its clinical significance was uncertain. With maternal dengue and compatible clinical features, neonatal dengue was clinically diagnosed, while perinatal transmission was considered likely but not definitively proven in the absence of neonatal RT-PCR or paired serology. From days 5–10, the infant developed fever and marked thrombocytopenia (nadir 29 × 10⁹/L) without hemodynamic instability. Intravenous immunoglobulin (1 g/kg) was given for immune modulation, and a short azithromycin course targeted atypical bacteria. By day 14, respiratory findings, inflammatory markers, and platelet count improved, and the infant was discharged in stable condition with arranged follow-up.ConclusionsNeonatal dengue should be considered in infants born to mothers with recent dengue in endemic settings. A structured approach—early supportive care, targeted testing (NS1/RT-PCR/serology), careful interpretation of neonatal coagulation and platelet trends, and judicious antimicrobial use—can aid differentiation from overlapping perinatal lung disease and guide timely management.